Sosialisasi Politik Bagi Pemilih Pemula Siswa Sekolah Menengah Atas Negeri 1 Palangka Raya - Jovano Deivid Oleyver Palenewen (RUANG KOMUNITAS: Jurnal Pengabdian Masyarakat, 2023)
Indonesia is a democratic country that requires elections to serve as a political space for the people to express their political rights. This principle emphasizes the importance of community participation in voting, including groups of first-time voters. Community service is one of the Tri Dharma of higher education through political socialization which can contribute to increasing community participation, including first-time voters. SMA Negeri 1 Palangka Raya students are a partner community for political socialization for first-time voters. They are the younger generation who must be involved in political agendas, including elections and local elections. If they are 17 years old, they can use their right to vote both in elections and local elections and they are categorized as first-time voters. This community service has been carried out in the form of political socialization for beginner voters at SMA Negeri 1 Palangka Raya.